Formulation development and in-vitro evaluation of floating sintered matrix tablets of Cefpodoxime Proxetil using carnauba wax - Shailaja Thoudoju; Asema Sultana; Latha Kukati; Naseeb Basha shaik; Aisha Rahman; Ahmed Unisha Affrin Shaik; Preeti Kulkarni (German Journal of Pharmaceuticals and Biomaterials, 2024)
The current study is centered on the development of floating sintered matrix tablets of Cefpodoxime proxetil for gastro-retentive delivery, employing carnauba wax as a release retardant. The hot melt granulation method was employed for the preparation of floating tablets. Carnauba wax was employed as a rate-controlling polymer and found to be well-suited for physical sintering. Menthol served as a buoyant agent. The compatibility between Cefpodoxime and carnauba wax was determined through Fourier Transform Infrared Spectroscopy and Differential Scanning Calorimetry studies. The tablets exhibited floating without lag time due to the evaporation of menthol during sublimation, and the floating duration exceeded > 24 h. The F3 formulation was optimized based on in-vitro dissolution studies of 97.09 ± 0.29% over 8 h. The F2, F3, and F4 formulations underwent physical sintering at temperatures of 50, 60, and 70 ºC for varying durations. The physicochemical parameters and in-vitro dissolution studies were evaluated for the sintered tablets. The F3S formulation includes carnauba wax and drug in a ratio of 0.6:1 with 8% w/w menthol, was subjected to a temperature of 70 ºC for 2 h, exhibited favorable floating properties, and improved dissolution profile of 81.05 ± 0.15% within a 12 h timeframe. Model-dependent kinetics demonstrated that drug release exhibited zero-order kinetics and Higuchi Fickian diffusion mechanism, suggesting that drug release was governed by diffusion through the matrix. The successful preparation of floating sintered matrix tablets of cefpodoxime proxetil was achieved through the process of physical sintering with sustained drug release.